2018
DOI: 10.4066/biomedicalresearch.29-17-3642
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hyaline membrane disease in preterm infants after prenatal corticosteroid prophylaxis

Abstract: Premature birth is a serious medical, social and economic problem. Its consequences are multiple health complications leading to high neonatal mortality worldwide. Respiratory insufficiency and surfactant deficiency significantly increase the risk of developing Hyaline Membrane Disease (HMD) and other forms of Respiratory Distress (RDS). These are the most common causes of death in premature babies. In prenatal and neonatal medicine, new and adaptive prophylaxis is being implemented to reduce the risk of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In this study Pearson chi-square test p value highly significant of female gender with complications of HMD. Outcome newborns of hyaline membrane disease were dead in more than half of the sample (52%), Bulgaria study in 2018 mentioned the goal of effective corticosteroid prophylaxis is to reduce mortality, reduce complications in prenatal new-born babies same results in this study in which Dexamethasone was used [25].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In this study Pearson chi-square test p value highly significant of female gender with complications of HMD. Outcome newborns of hyaline membrane disease were dead in more than half of the sample (52%), Bulgaria study in 2018 mentioned the goal of effective corticosteroid prophylaxis is to reduce mortality, reduce complications in prenatal new-born babies same results in this study in which Dexamethasone was used [25].…”
Section: Discussionsupporting
confidence: 53%
“…A retrospective study of 167 preterm infants was conducted, of which 89 (53.3%) had prophylaxis with Dexamethasone, in 25 (15%) of preterm infants, there was a Hyaline Membrane Disease (HMD) and 101 (60.5%) developed other forms of Respiratory Distress Syndrome (RDS). The results obtained show that the incidence of HMD in preterm infants is mediated by the early gestational age and advanced age of the mother, and decreased by corticosteroid therapy [25]. The study showed that the premature birth is a serious medical, social and economic problem.…”
Section: Currently Recommended Treatment Modalities For Hmd Include Oxygen Therapy Continuousmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study proportion of hyaline membrane disease was 40%, this is consistent with study conducted in Iraq, 42.2% [ 17 ], in Black lion Hospital, Ethiopia 42.9% [ 41 ]. But, higher than study conducted in Nigeria, 26.2% [ 14 ], in Bulgaria, 15% [ 42 ], in Nepal 17.8% [ 43 ], in Jimma Ethiopia 11.9% [ 20 ].This could be the current study include only preterm neonates. In addition, the study conducted in Bulgaria was conducted among preterm neonate whose mother took dexamethasone.…”
Section: Discussionmentioning
confidence: 94%